Making regional facility location decisions: the example of Hospital do Oeste Norte, Portugal - Jorge Gonçalves; J. Antunes Ferreira; Beatriz Condessa (Geospatial Health, 2014)
This paper seeks to contribute to the debate on the decision-making process for the location of large public facilities, responding to the growing demand for greater rationality in public investment whilst still offering services of quality and addressing the problem of spatial friction. The specific problem analysed in this paper is the need to define the best location for a public hospital in a particular region of Portugal. The singularity of the approach adopted lies above all in the seg- mentation into macro-location and micro-location.